Assessment of Heavy Metal Contamination and Potential Health Risk of Selected Fish Species in Dhaka District (Bioresearch Communications, 2024)
Fish is a rich source of quality protein and fatty acids. Bangladesh's average daily fish consumption is 67.8 grams per people. Fish species are also prone to heavy metal contamination from their surrounding environment. The main objective of this research was to assess the degree of risk associated with the consumption of various fish species in Dhaka, Bangladesh. Three fish species—Tilapia (Oreochromis mossambicus), Shorputi (Systomus sarana), and Mola (Amblypharyngodon mola)—from three local markets in Savar Union, Dhaka, Bangladesh, were selected for analysis. The Kjeldahl technique, Folch method, and several formulae were used to determine the protein, fat, ash, and moisture content for the proximate analysis. The concentration of heavy metals was determined using Atomic Absorption Spectrophotometry (AAS). The estimated daily intake (EDI), target hazard quotient (THQ), total target hazard quotient (TTHQ), hazard index (HI), and cancer risk (CR) were used to evaluate the danger to human health. Tilapia had the highest moisture and lipid content, whereas Shorputi and Mola had the highest protein and ash contents, ranging from 20.77% to 18.16%, respectively. The mean concentration of heavy metals in fish was determined to be Pb>Ni>Cr>Cd in this study. Every fish species had extremely high levels of lead (Pb), with the Shorputi fish having the highest levels. Fish from the Shorputi species had the highest EDI value. Pb>Ni>Cr>Cd was the trace element EDI for adults. Among all species, only Pd had a THQ value higher than 1. The CR value across all species were within E-3 and E-6 range, while the HI value was >1. In conclusion, the highest average Pb concentrations were detected in Shorputi, while the highest amounts of Cd, Cr, and Ni were observed in Tilapia. The findings of this study recommended that the Bangladeshi government regularly assess the levels of dangerous heavy metal and metalloid contamination in the daily meals of its citizens in order to enforce regulatory limits and determine the likelihood of long-term exposure.Bioresearch Commu. 10(2): 1524-1531, 2024 (July)